2001
DOI: 10.1038/sj.ijo.0801589
|View full text |Cite
|
Sign up to set email alerts
|

A genetic analysis of weight and overweight in 4-year-old twin pairs

Abstract: OBJECTIVE: Although many twin and adoption studies document genetic in¯uence on individual differences in weight, much less is known about genetic in¯uences on overweight, about the genetic links between weight and overweight, or about the origins of weight and overweight in childhood, an age that might provide a good target for prevention of obesity. We tested the hypothesis that, in early childhood, overweight is as heritable as weight and that weight and overweight are linked genetically. DESIGN: Model-®tti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
42
2
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(49 citation statements)
references
References 22 publications
3
42
2
2
Order By: Relevance
“…An intriguing finding from existing studies is the apparent evidence for shared environmental influences on eating behavior, which implicates the home environment vis-à-vis the development of child eating patterns. This is in contrast to most twin studies of BMI, which generally fail to find a significant effect of the home environment (although some studies do report home environmental influences on BMI in pediatric samples 40,41 ).…”
contrasting
confidence: 50%
“…An intriguing finding from existing studies is the apparent evidence for shared environmental influences on eating behavior, which implicates the home environment vis-à-vis the development of child eating patterns. This is in contrast to most twin studies of BMI, which generally fail to find a significant effect of the home environment (although some studies do report home environmental influences on BMI in pediatric samples 40,41 ).…”
contrasting
confidence: 50%
“…In a large study of 3636 four year old twins, the researchers found that genetic factors contributed substantially to individual differences in weight (Koeppen-Schomerus, Wardle, & Plomin, 2001). In addition, a study of 106 overweight children age 3 to 18 years found that obesity in one or both parents correlated with a higher percentage of ideal body weight (p=0.01) (Anavian, Brenner, Fort, & Speiser, 2001).…”
Section: Genetic Factorsmentioning
confidence: 99%
“…Behavioural twin studies have indicated heritability of between 14 % and 69% for indices of eating style such as daily energy intake, meal intake, energy density of the diet, pre-and postmeal hunger and pre-meal stomach contents (94)(95)(96) , while heritability for three-factor eating questionnaire and Dutch eating-behaviour questionnaire scales range from 0% to 59% depending on study population and the measure used (97)(98)(99) . However, since there is evidence for heritability of obesity in children (100) as well as adults (101) , and some suggestion that shared environmental influence may be stronger in young children, who still share the family home (102) , independent investigation of heritability of appetite in children is warranted.…”
Section: Genetic Influences On Appetitive Traitsmentioning
confidence: 99%